2020
DOI: 10.1002/ejoc.202000093
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Dyes with Large Stokes Shifts Based on Benzo[1,2‐d:4,5‐d']bis([1,3]dithiole) (“S4‐DBD Dyes”)

Abstract: We report on a further development of [1,3]‐dioxolo[4.5‐f]benzodioxole (DBD) fluorescent dyes by replacement of the four oxygen atoms of the heterocyclic core by sulfur atoms. This variation causes striking changes of the photophysical properties. Whereas absorption and emission significantly shifted to longer wavelength, the fluorescence lifetimes and quantum yields are diminished compared to DBD dyes. The latter effect is presumably caused by an enhanced intersystem crossing to the triplet state due to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…A study on 4,5‐dimethoxyacridone ( 12 ) indicated that methoxy groups reduced quantum yield compared to the unsubstituted acridone ( 2 ) (0.410→0.100). All of the fluorescent compounds showed extremely large Stokes ‐shifts compared to the reported dyes [46–54] . This advantageous photophysical property can reduce interferences from self‐absorption and auto‐fluorescence, thus provides outstanding sensitivity and resolution for optochemical devices.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…A study on 4,5‐dimethoxyacridone ( 12 ) indicated that methoxy groups reduced quantum yield compared to the unsubstituted acridone ( 2 ) (0.410→0.100). All of the fluorescent compounds showed extremely large Stokes ‐shifts compared to the reported dyes [46–54] . This advantageous photophysical property can reduce interferences from self‐absorption and auto‐fluorescence, thus provides outstanding sensitivity and resolution for optochemical devices.…”
Section: Resultsmentioning
confidence: 93%
“…All of the fluorescent compounds showed extremely large Stokes-shifts compared to the reported dyes. [46][47][48][49][50][51][52][53][54] This advantageous photophysical property can reduce interferences from self-absorption and autofluorescence, thus provides outstanding sensitivity and resolution for optochemical devices. Compounds with large Stokesshifts, especially functionalizable-group-containing derivatives, which are reported herein, can have great importance for practical applications and are in the focus of very recent research activities.…”
Section: Fluorescence Properties Of New 9-substituted Acridine Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…This causes a significant lowering of the fluorescence quantum yields and lifetimes [7b] . Moreover, the quite efficient synthesis of S 4 ‐DBD dyes mandatorily requires the use of extremely malodorous tert ‐butylthiol [7a] . It should be noted that very recently an alternative route has been published [7d] .…”
Section: Introductionmentioning
confidence: 99%
“…Benzo[1,2-d;4,5-d′]bis[1,3]dithioles 1 ( Figure 1 ) have emerged as important building blocks for a range of functional materials. For example benzo[1,2-d:4,5-d′]bis[1,3]dithiole-based fluorescent dyes (“S4 DBD dyes” 2 ) exhibit large stokes shifts making them promising candidates for super-resolution microscopy such as stimulated emission depletion (STED) microscopy [ 1 , 2 ]. Moreover, conjugated polymers 3 consisting of such building blocks show fluorescence response upon oxidation rendering these materials interesting for oxidant sensing [ 3 ].…”
Section: Introductionmentioning
confidence: 99%